Molecular identification of rhamnolipids produced by Pseudomonas oryzihabitans during biodegradation of crude oil - Hosseini, Saman; Sharifi, Rouhallah; Habibi, Alireza; Ali, Qurban (Frontiers in Microbiology, 2024)
The ability to produce biosurfactants plays a meaningful role in the bioavailability of crude oil hydrocarbons and the bioremediation efficiency of crude oil-degrading bacteria. This study aimed to characterize the produced biosurfactants by Pseudomonas oryzihabitans during the biodegradation of crude oil hydrocarbons.The biosurfactants were isolated and then characterized by Fourier transform infrared (FTIR), liquid chromatography-mass-spectrometry (LC-MS), and nuclear magnetic resonance spectroscopy (NMR) analyses.The FTIR results revealed the existence of hydroxyl, carboxyl, and methoxyl groups in the isolated biosurfactants. Also, the LC-MS analysis demonstrated a main di-rhamnolipid (lrhamnopyranosyll-rhamnopyranosyl-3-hydroxydecanoyl-3-hydroxydecanoate, Rha-Rha-C10-C10) along with a mono-rhamnolipid (l-rhamnopyranosyl-b-hydroxydecanoylb-hydroxydecanoate, Rha-C10-C10). In agreement with these findings, the NMR analysis confirmed the aromatic, carboxylic, methyl, sulfate moieties, and hexose sugar in the biosurfactants. The emulsion capacity of the biosurfactants decreased the surface tension of the aqueous system from 73.4 mN m -1 to around 33 mN m -1 at 200 mg L -1 as the critical micelle concentration. The emulsification capacity of the biosurfactants in the formation of a stable microemulsion for the diesel-water system at a wide range of pH (2-12), temperature (0-80ᵒC), and salinity (2-20 g L -1 of NaCl) showed their potential use in oil recovery and bioremediation through the use of microbial enhancement.Discussion: This work showed the ability of Pseudomonas oryzihabitans NC392 cells to produce rhamnolipid molecules during the biodegradation process of crude oil hydrocarbons. These biosurfactants have potential in bioremediation studies as eco-friendly and biodegradable products, and their stability makes them optimal for areas with extreme conditions.